The catastrophe of the artistic space in the story "The Day when the World collapsed" by R. Seisenbaiev (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
On the base of the story by Rollan Seysenbayev «The Day, when the World has collapsed» the author analyzes catastrophism as the ideological and stylistic literary phenomenon. The author systematically and comprehensively analyzes the trends and means of artistic embodiment of catastrophism, primarily its technocratic modification. The article reveals the catastrophism as the catalyst of semantic and structural transformation, existential modes and author intentions. The author emphasizes the typological affinity of artistic images of R. Seysenbayev’s story «The Day, when the World has collapsed» and the works of Chernobyl theme.
Keywords: catastrophism; catastrophism discourse; , technocratic model of catastrophism; documentation; eschatology; existentialism; typological coincidences